Applying Importance-Performance Analysis to Identify Strategic Factors Enhancing User Satisfaction in Dana - Adibah Dewi Satriani; Asif Faroqi; Tri Puspa Rinjeni (Komunitas Dosen Indonesia, 2025)
The use of digital wallets in Indonesia has grown significantly alongside increasing public demand for fast, secure, and practical financial transactions. One of the widely used applications is Dana. However, user satisfaction with its services still requires a comprehensive evaluation to ensure continued usage. This study aims to measure and analyze user satisfaction with the Dana application by integrating the End User Computing Satisfaction (EUCS) model and the Importance-Performance Analysis (IPA) method. This research employed a quantitative approach by distributing online questionnaires to 403 respondents. The research instrument was tested for validity and reliability, and the data were analyzed using IPA to map service attributes based on their perceived importance and performance. The results show that attributes such as system security, content completeness, and information accuracy fall into the high-priority quadrant (Quadrant I), indicating that they are highly important but currently underperforming. Meanwhile, attributes like content format and timeliness meet user expectations and should be maintained. The study concludes that Dana’s development team should prioritize improvements in the aspects that most significantly affect user satisfaction. These findings are expected to serve as a strategic foundation for decision-making in enhancing service quality, while also contributing to the academic literature on evaluating digital financial applications.